Psychological Impact of Atopic Eczema - Intervention with Homoeopathy (Homoeopathy for All, 2023)
Atopic eczema (dermatitis), a type of eczema, is a chronic  inflammatory skin disease posing  a significant burden on health  care resources. It affects up to 3%  of adults; recent data show that  its prevalence is still increasing,  especially in low socio economic  countries. There is limited evidence  to support the use of conventional  treatment of this condition. With  reference to the current scenario  prevalence of atopic dermatitis in  adults is increasing. Homoeopathy  treats the individual in disease and  not the disease alone and holistically  helps the patient in need. Thus by  striking at the root of the problem  patient can be relieved from further  remission of suffering.
Keywords: chronic; Homoeopathy; patient